2015
DOI: 10.1002/hup.2454
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cocaine exposure and child outcomes: a conference report based on a prospective study from Cleveland

Abstract: Objective The study aims to describe developmental outcomes from a longitudinal prospective cohort (Cleveland study) of prenatally cocaine-exposed (CE) infants. Methods Two hundred eighteen CE and 197 nonexposed infants were enrolled at birth and followed through mid-adolescence. Birth CE status was determined by interview and biologic measures. Multiple demographic, drug, and environmental correlates were controlled. Standardized, normative, reliable measures of fetal growth, intelligence quotient (IQ), beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Elevated blood lead levels, which often co-occur within low socioeconomic status households and, therefore, at high rates in our sample (Min et al, 2009), are also associated with increased risk of behavioral problems in childhood through early adulthood in the general population (Wasserman et al, 1998; Burns et al, 1999; Lane et al, 2008; Wright et al, 2008), and were found to be related to alcohol use in adolescents with PCE (Minnes et al, 2014a,b). Other caregiver characteristics known to independently influence behavioral outcomes include caregiver psychological distress, receptive vocabulary skills, non-verbal reasoning ability and quality of the home environment (Bennett et al, 2008; Singer et al, 2008; Singer et al, 2015). Generally, poor environmental and socioeconomic conditions are often prevalent among parents with substance use disorders and are important factors to consider in evaluating the relationship between PCE and teen substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated blood lead levels, which often co-occur within low socioeconomic status households and, therefore, at high rates in our sample (Min et al, 2009), are also associated with increased risk of behavioral problems in childhood through early adulthood in the general population (Wasserman et al, 1998; Burns et al, 1999; Lane et al, 2008; Wright et al, 2008), and were found to be related to alcohol use in adolescents with PCE (Minnes et al, 2014a,b). Other caregiver characteristics known to independently influence behavioral outcomes include caregiver psychological distress, receptive vocabulary skills, non-verbal reasoning ability and quality of the home environment (Bennett et al, 2008; Singer et al, 2008; Singer et al, 2015). Generally, poor environmental and socioeconomic conditions are often prevalent among parents with substance use disorders and are important factors to consider in evaluating the relationship between PCE and teen substance use.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed that children prenatally exposed to COC are more likely to manifest cognitive deficits in subareas of IQ (visuospatial skills, general knowledge, and arithmetic skills) but that they did not exhibit a lower global IQ (Singer et al, 2004). In a recent study, the same researchers observed a negative impact of prenatal COC exposure on perceptual reasoning IQ; however, the children's global IQ remained unaffected (Singer et al, 2015). Future studies should accordingly specifically target various IQ subdomains to draw firm conclusions.…”
Section: Iq and Learningmentioning
confidence: 91%
“…Cocaine use during pregnancy is associated with placental abruption, premature rupture of membranes, preterm labor, preterm delivery, maternal seizures, maternal hypertension, and uterine contractions . Poor behavioral adjustment and executive function through adolescence may result from perinatal cocaine exposure . Similarly, infants born to women using opiates are at risk for neonatal abstinence syndrome, which is characterized by hyperactivity of the central and autonomic nervous systems .…”
Section: Introductionmentioning
confidence: 99%